2023
DOI: 10.1007/s13402-023-00857-y
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion in colorectal cancer: mechanisms of action and clinical relevance

Hao Wang,
Ruixue Huo,
Kexin He
et al.

Abstract: Background In recent years, the significance of the nervous system in the tumor microenvironment has gained increasing attention. The bidirectional communication between nerves and cancer cells plays a critical role in tumor initiation and progression. Perineural invasion (PNI) occurs when tumor cells invade the nerve sheath and/or encircle more than 33% of the nerve circumference. PNI is a common feature in various malignancies and is associated with tumor invasion, metastasis, cancer-related pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 196 publications
0
4
0
Order By: Relevance
“…Neural invasion refers to tumor cells invading the nerve sheath or the presence of tumor cells within the nerve sheath, which is associated with tumor invasion, metastasis, cancer-related pain, and poor clinical outcomes. The New England Journal of Medicine has also considered neural invasion as pathological evidence of early metastasis in colorectal cancer, being independently associated with low survival rates ( 20 ). This study confirmed that TNM stage III and neural invasion are independent risk factors for DFS in patients after radical rectal cancer surgery, and incorporated them into the predictive model.…”
Section: Discussionmentioning
confidence: 99%
“…Neural invasion refers to tumor cells invading the nerve sheath or the presence of tumor cells within the nerve sheath, which is associated with tumor invasion, metastasis, cancer-related pain, and poor clinical outcomes. The New England Journal of Medicine has also considered neural invasion as pathological evidence of early metastasis in colorectal cancer, being independently associated with low survival rates ( 20 ). This study confirmed that TNM stage III and neural invasion are independent risk factors for DFS in patients after radical rectal cancer surgery, and incorporated them into the predictive model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in our study, perineural invasion frequency was higher in the rsCRC group, which might explain the lower survival and higher mortality reported. Many studies reported a significant association between perineural invasion and bad CRC prognosis and outcome, including higher recurrence, lower DFS, and OS, requiring adjuvant therapy [ 28 ]. Though no reports in the literature described specifically the perineural invasion status in the rsCRCs versus ocCRCs, perineural invasion reports are higher in rectal cancer compared to colon cancer and reflect a bad prognosis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion (PNI) is a common pathological feature found in cancers of nerverich regions, such as prostate cancer, pancreatic cancer, and head and neck cancers [40]. PNI has long been a focus of research because it is considered a route of metastasis in addition to the vascular and lymphatic channels, and multiple studies have associated PNI with an unfavorable prognosis [40][41][42][43]. In this chapter, the main features and mechanisms of PNI are presented, and the limitations in diagnosis are also discussed.…”
Section: Perineural Invasionmentioning
confidence: 99%